Relative validation of the adapted Mediterranean Diet Score for Adolescents by comparison with nutritional biomarkers and nutrient and food intakes: the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) study. Issue 13 (17th June 2019) - Aparicio-Ugarriza, Raquel; Cuenca-García, Magdalena; Gonzalez-Gross, Marcela; Julián, Cristina; Bel-Serrat, Silvia; Moreno, Luis A; Breidenassel, Christina; Kersting, Mathilde; Arouca, Aline B; Michels, Nathalie; Mouratidou, Theodora; Manios, Yannis; et al.
Abstract: Objective: To investigate whether adherence to the adapted Mediterranean Diet Score for Adolescents (MDS_A) and the adapted Mediterranean Diet Quality Index for Adolescents (KIDMED_A) is associated with better food/nutrient intakes and nutritional biomarkers. Design: The Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) study is a cross-sectional study aiming to obtain comparable data on a variety of nutritional and health-related parameters in European adolescents aged 12·5–17·5 years. Setting: Nine European countries. Participants: European adolescents ( n 2330) recruited to the HELENA study. Dietary intake was obtained with 24 h dietary recalls, an FFQ and a Food Choices and Preferences questionnaire. MDS_A was calculated as a categorical variable using cut-offs (MDS_A), as a continuous variable (zMDS_A) and with energy adjustments (zEnMDS_A). The KIDMED_A score was also calculated. Results: Multilevel linear regression analysis showed positive associations for zMDS_A and KIDMED_A with serum levels of vitamin D, vitamin C, plasma folate, holo-transcobalamin, β-carotene and n -3 fatty acids, while negative associations were observed with trans -fatty acid serum levels. For categorical indices, blood biomarkers showed few significant results. zMDS_A and KIDMED_A showed positive associations with vegetables and fruits intake, and negative associations with energy-dense and low-nutritious foods. zMDS_A and KIDMED_A were positively associated with all macronutrients, vitamins and minerals (all P < 0·0001), except with monosaccharides and PUFA for KIDMED_A and cholesterol for both indices ( P < 0·05). Conclusions: zMDS_A and KIDMED_A have shown the strongest associations with the dietary indicators and biomarkers that have been associated with the Mediterranean diet before, and are therefore considered the most appropriate and valid Mediterranean diet scores for European adolescents.